New augite geothermometer for nakhlites - A. M. Fioretti; M. C. Domeneghetti; M. Alvaro; L. Marinangeli; F. Camara (Wiley, 2014)
Introduction: nakhlites, together with shergottites and chassinites constitute the “SNC” group of Martian meteorites. MIL 03346 is a nakhlite, that was found at Miller Range, in Antarctica and is mainly composed of clinopyroxene (79%), with minor olivine (1%), and 20% vitrophyric intercumulus material [1,2]. The clinopyroxene is augite with a homogeneous core (En36Fs24Wo40) and an iron enriched rim (En8Fs64Wo28). Since the first modern petrologic studies of Nakhla, the nakhlite group of meteorites has been interpreted as augite-rich cumulate igneous rocks, derived from basaltic magma, that erupted onto the surface of Mars [3,4]. The relative low closure temperature (Tc) of ca. 500 (±100)°C calculated for MIL 03346 by [5] with the available geothermometer [6] would correspond to a slow cooling rate that is in disagreement with the petrologic evidence for an origin from a fast cooled lava flow. Geothermometer calibration: ex-situ annealing experiments combined with high-resolution single-crystal X-ray diffraction (HR-SC-XRD) on crystals from MIL 03346 clearly showed that the degree of order remained unchanged at 600°C thus suggesting that the actual Tc is close to this temperature. We then undertook an ex situ annealing experiments combined with HR-SC-XRD at 600, 700, 800 and 900 °C until the equilibrium in the Fe2+-Mg exchange on two crystals from exactly the same fragment of MIL 03346 sample in order to obtain a new geothermometer for augites from Martian nakhlites: lnkD = -4421(±561)/T(K) + 1.46(±0.52) (R2=0.988) where kD = [(Fe2+M1)(MgM2) / (Fe2+M2)(MgM1)] Results: applying this new equation to MIL 03346 the closure temperature resulted to be 605(84)°C about 100°C higher than that calculated with previously available calibration (i.e. Brizi et al. 2000). However, this closure temperature of 605°C is still lower than expected based on petrologic evidences and suggests that MIL 03346 clinopyroxene bears record of a thermal event that postdates, or is superimposed on, the natural cooling path of the host lava ...